Climate change and philosophy : transformational possibilities - Irwin, Ruth, 1968- (Continuum studies in philosophy., 2010)
This is a hugely important collection of essays that examines the significance of philosophical inquiry in relation to the issue of climate change. "Climate Change and Philosophy" presents ten original essays by an international team of expert contributors, exploring the important contribution philosophical inquiry can make to contemporary debates to do with climate change and the global environment. Examining this hugely topical issue through the lens of environmental philosophy, political theory, philosophy of technology, philosophy of education and feminist theory, these essays in.